2023
DOI: 10.1177/20503121231193602
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of podoconiosis in sub-Saharan Africa: A systematic review and meta-analysis

Temesgen Lera Abiso,
Amene Abebe Kerbo,
Eskinder Wolka Woticha

Abstract: Objective: Podoconiosis, one of the neglected tropical diseases (NTDs), affects barefoot people in impoverished regions and contributes to poverty by having negative impacts on economic output, education, and disability. People who have the disease waste nearly half of all of their productive workdays. There is limited evidence available on prevalence of podoconiosis in sub-Saharan Africa (SSA). Therefore, the aim of this research was to determine the pooled prevalence of podoconiosis in the SSA over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…Walking barefoot was identified as a risk factor for podoconiosis. This is consistent with findings from studies in other sub-Saharan Africana countries including Ethiopia and Kenya [ 15 19 ]. Walking barefoot is known to predispose to irritant volcanic red clay soils [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Walking barefoot was identified as a risk factor for podoconiosis. This is consistent with findings from studies in other sub-Saharan Africana countries including Ethiopia and Kenya [ 15 19 ]. Walking barefoot is known to predispose to irritant volcanic red clay soils [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, older participants showed higher odds of podoconiosis compared to those under 25 years old. This aligns with findings from studies in sub-Saharan Africa [ 15 , 18 , 19 , 21 ]. This trend may be attributed to prolonged exposure to irritant soils as individuals age.…”
Section: Discussionsupporting
confidence: 89%